1988
DOI: 10.1210/endo-122-5-1991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Limited Exposure of Rabbit Chondrocyte Cultures to Parathyroid Hormone and Dibutyryl Adenosine 3′,5′-Monophosphate on Cartilage-Characteristic Proteoglycan Synthesis*

Abstract: Treatment of rabbit chondrocyte cultures with PTH or (Bu)2cAMP for 30 h increased by 2- to 3-fold the incorporation of [35S]sulfate and 3H radioactivity with glucosamine as the precursor into large chondroitin sulfate proteoglycans characteristically found in cartilage matrix. However, PTH and (Bu)2cAMP did not increase either [35S]sulfate incorporation into small proteoglycans or the incorporation of 3H radioactivity into hyaluronic acid and other glycosaminoglycans. PTH and (Bu)2cAMP also increased the incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Interestingly, a relationship between cAMP and terminal differentiation and calcification of cultured chondrocytes has been clearly established (13), which could support the involvement of AM in the regulation of this process through its cAMP-dependent signal transduction system. Various other active factors that affect chondrocyte differentiation also increase the cAMP concentration in chondrocytes (17). The localization of AM, its mRNA, and the mRNA of its receptor to the growing skeletal structures and the fact that AM elicits its biological actions via the elevation of cAMP levels suggest an involvement of AM in embryonic chondrocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a relationship between cAMP and terminal differentiation and calcification of cultured chondrocytes has been clearly established (13), which could support the involvement of AM in the regulation of this process through its cAMP-dependent signal transduction system. Various other active factors that affect chondrocyte differentiation also increase the cAMP concentration in chondrocytes (17). The localization of AM, its mRNA, and the mRNA of its receptor to the growing skeletal structures and the fact that AM elicits its biological actions via the elevation of cAMP levels suggest an involvement of AM in embryonic chondrocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Although fewer studies have been conducted on the effects of PTH on cartilage cell growth and differentiation, it has been reported that this hor¬ mone is involved in cartilage development (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in aggrecan synthesis was observed when the cells were treated for 20 or 4 h followed by a 16-h recovery in the absence of PTH. Previous studies using adult rabbit chondrocytes have demonstrated an effect of PTH only after a 24-h treatment and not within a 4-h treatment (25). These differences may be a reflection of species or developmental age or both.…”
Section: Fig 8 Reciprocal Relationship Between Aggrecan and Ig-fbp-mentioning
confidence: 91%